ANALISIS POLA KOMUNIKASI PADA SISWA TUNARUNGU DI SMALB DHARMA ASIH KOTA PONTIANAK - Saputri, Anggi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Absract Communication is a process whereby a person or multiple persons, groups or organizations, create and use information in order to connect with the environment and others. Communication can take place with anyone and at any time without exception whether it is poor, rich, educated or not, as well as normal or not even a special need like a hearing impaired. A general problem in this study relates to the pattern of communication in students with special needs deaf.  A general problem in this study relates to the pattern of communication in students with special needs deaf. The approach used in this research is qualitative approach with descriptive method. Data collection techniques used are observation techniques, interviews, and documentation. The results showed that, the deaf student communication process consists of 3 communication patterns namely verbal communication, nonverbal communication and total communication. Verbal communication forms of communication that include "oral, written, and two-way communication, through electronic and face-to-face communication". Nonverbal communication involves the communication process with "the use of body language, and the use of touch on the limbs. As for communication total communication process that includes communication process with three method that is method "manual component, oral component, and aural component.               Keyword : Communication, Patterns,  In Deaf Students